Photodynamic therapy alone and in combined modality treatment for locally advanced basal cell skin cancer - E. V. Yaroslavtseva-Isaeva; M. A. Kaplan; V. N. Kapinus; I. S. Spichenkova; A. M. Shubina; E. V. Goranskaya (Biomedical Photonics, 2019)
Outcomes after photodynamic therapy (PDT) in 33 patients with basal cell skin cancer Т3-Т4N0M0 primary stage are represented in the article. The irradiation was performed distantly 3h after intravenous injection of photosensitizer photolon with dose 0.8-1.0 mg/kg; light dose accounted for 200-400 J/cm2. Distant PDT was applied as monotherapy or in combination with electrochemical lysis, radiotherapy or interstitial PDT. 84.6% of patients with Т3N0M0 stage basal cell skin carcinoma had complete regression, 15.4% of patients – partial regression. The treatment for Т4N0M0 stage basal cell skin carcinoma was palliative and in 100% of cases it allows to shrink the tumor (defined as partial tumor regression), retard the progression time, improve quality of life. Interstitial PDT and electrochemical lysis improved the efficacy of distant PDT (increased volume of tumor destruction) and, thus, allowed to decrease treatment period. Combination of PDT with radiotherapy allowed to decrease radiation dose for 20-30% and, thus, to decrease the risk of radiation-induced complications.